1996
DOI: 10.1021/np9601420
|View full text |Cite
|
Sign up to set email alerts
|

Biogenetic Conversion of Tetrahydroisoquinoline−Monoterpene Glucosides into Benzopyridoquinolizine Alkaloids of Alangium lamarckii

Abstract: The biogenetic conversion of alangiside (6), a major tetrahydroisoquinoline−monoterpene glucoside of Alangium lamarckii, into (+)-alangimaridine (1), one of the benzopyridoquinolizine alkaloids of the same plant, was carried out confirming its absolute configuration. Isoalangimarine (3) and its possible precursor (+)-isoalangimaridine (19) were synthesized from 3-O-demethyl-2-O-methylalangiside (11).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Previously, alangisides have been chemically transformed into the skeleton of alangimaridines, benzopyridoquinolizine alkaloids from Alangium lamarckii, which supports alangisides as biogenetic precursors of these alkaloids. [22] In the case of protoberberine alkaloids 1 and 2, their biosynthesis may involve the hydrolysis of alangiside 9, ring cleavage to give the intermediate A, and a bond rotation in A to furnish the intermediate B (Scheme 1). The intermediate B undergoes cyclization, dehydration, dehydrogenation, and oxidation to give alangiumkaloid A (1), which is further reduced to yield alangiumkaloid B (2; Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, alangisides have been chemically transformed into the skeleton of alangimaridines, benzopyridoquinolizine alkaloids from Alangium lamarckii, which supports alangisides as biogenetic precursors of these alkaloids. [22] In the case of protoberberine alkaloids 1 and 2, their biosynthesis may involve the hydrolysis of alangiside 9, ring cleavage to give the intermediate A, and a bond rotation in A to furnish the intermediate B (Scheme 1). The intermediate B undergoes cyclization, dehydration, dehydrogenation, and oxidation to give alangiumkaloid A (1), which is further reduced to yield alangiumkaloid B (2; Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The dichloromethane extract of the stems of A. salviifolium was subjected to columnc hromatography on silica gel, Sephadex LH-20, preparative TLC, and semipreparative RP-18 HPLC to provide twelve cardinane sesquiterpenes, of which seven are new compounds, alangenes A-G (1)(2)(3)(4)(5)(6)(7). The known compounds were identified as mansonone H( 8 ), [5,6] mansonone E (9), [5,7] mansonone G( 10), [8] dehydrooxoperezinone (11), [9] and (S)-(À)-lacinilene C( 12) [10,11] by comparison of their physical and spectroscopic data (NMR and MS) with those reported in the literature (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Various parts of this plant are used in Indian folk medicine. [1] In Thailand, the wood is used as at raditional medicine for the treatment of hemorrhoids, and as at onic, while the stem bark and fruits are used as an expectorant, and as an anti-asthmatic, antidiarrheal, anthelmintic, and antiflatulent medicine. [2] Phytochemical studies on this plant have shown the presence of iridoid glycosides, phenolic glycosides and several types of alkaloids, that is, tetrahydroisoquinoline monoterpene glucoside, tetrahydro-b-carboline monoterpene glucoside, benzoquinolizine, protoberberine, benzopyridoquinolizine, and ipecac alkaloids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations